Health‐related quality of life association with weight change in type 2 diabetes mellitus: perception vs. reality. Issue 5 (11th April 2013) - Grandy, S.; Fox, K. M.; Bazata, D. D.; ,
Summary Aims This study compared health‐related quality of life (HRQOL) in adults with type 2 diabetes mellitus (T2DM) who reported their perception of weight change vs. actual weight change. Methods Respondents to the US Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes (SHIELD) 2008 survey were asked if they had lost, maintained or gained weight compared with 1 year earlier (perception). Respondents also provided their actual weight and completed the SHIELD WQ‐9 questionnaire to report how weight change affected 9 aspects of daily life. Perceived weight loss or gain was compared with measured weight change reported (2007 weight – 2008 weight) in those with T2DM. Results In respondents reporting weight loss (n = 762), 75.4% lost weight and 15.9% gained weight. For respondents reporting weight gain (n = 392), 70.2% gained weight and 19.6% lost weight. HRQOL did not differ between those who reported weight loss and actually lost weight vs. those who reported weight loss and actually gained weight (p > 0.05), except for self‐esteem (p = 0.004). HRQOL was similar for those who reported weight gain and actually gained weight vs. those who reported weight gain, but actually lost weight (p > 0.20). Respondents who had perceived weight loss had significantly better HRQOL than those who perceived that they had gained weight. Conclusions Perception of weight loss/gain may be as powerful as actual weight loss/gain in impacting HRQOL among adults with T2DM. Interventions that help individuals lose weight or perceive weight loss in addition to lowering glucose will assist in improving HRQOL.